2008
DOI: 10.1007/s10255-007-7055-0
|View full text |Cite
|
Sign up to set email alerts
|

Solvability of Navier-Stokes equations with leak boundary conditions

Abstract: The time-dependent Navier-Stokes equations with leak boundary conditions are investigated in this paper. The equivalent variational inequality is derived, and the weak and strong solvabilities of this variational inequality are obtained by the Galerkin approximation method and the regularized method. In addition, the continuous dependence property of solutions on given initial data is established, from which the strong solution is unique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…In this way different problems are studied (cf. [7,8,10,34,36,[38][39][40][41][42]55,61,62,66]). In [36] another equivalent variational formulation, where strain, pressure, velocity and rotation are unknown functions, also is given.…”
Section: Introductionmentioning
confidence: 99%
“…In this way different problems are studied (cf. [7,8,10,34,36,[38][39][40][41][42]55,61,62,66]). In [36] another equivalent variational formulation, where strain, pressure, velocity and rotation are unknown functions, also is given.…”
Section: Introductionmentioning
confidence: 99%
“…This Uzawa iteration method is based on the following equivalence relationship. It can be shown that Navier-Stokes type variational inequality problem (2.4) is equivalent to the following variational equation: 2 OUT OF MEMORY Table 2 Convergence of two-level Newton iteration VMS method with Re = 1000. From the view of computational cost, we can obviously observe by comparing Tables 1-2 that two-level Newton iteration VMS method saves CPU time than one-level VMS method, and obtains nearly the same approximation results.…”
Section: Program Implementationmentioning
confidence: 99%
“…The boundary conditions (1.2) are introduced by H. Fujita in [1]. Subsequently, some well-posedness problems for the steady and nonstationary problems are studied by many scholars, such as R. An, Y. Li and K. Li [2] H. Fujita [3][4][5], T. Kashiwabara [6], Y. Li and K. Li [7,8], Le Roux [9,10], F. Saidi [11], N. Saito [12] and references cited therein. Meanwhile, there also exist some works about the finite element methods for solving the numerical solution to the problem (1.1) and (1.2).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, many studies have focused on the properties of the solution of the resulting boundary value problem, for example, existence, uniqueness, regularity, and continuous dependence on data, for Stokes, Navier-Stokes and Brinkman-Forchheimer equations under such boundary conditions. Details can be found in [1,3,11,12,13,14,15,16,17,43,44,45,46] among others.…”
Section: Preliminaries and Weak Formulationsmentioning
confidence: 99%